A genre analysis of academic oral presentations of ESL undergraduates at a public university in Malaysia - Maktiar Singh, Kuldip Kaur (2019)
This study examined the rhetorical moves of academic oral presentations in both English language proficiency and discipline-based courses as a basis for investigating to what extent undergraduates transfer their genre knowledge from one course to another. The similarities and differences in rhetorical moves of oral presentations in both English language and discipline-based courses were identified. This is a descriptive study which employed both quantitative and qualitative methods. Using Swales’ CARS model (1990), the rhetorical moves of academic oral presentations were analysed. The sample comprised 20 group academic oral presentations from the English language and 20 group academic oral presentations from the discipline-based courses. The visuals in the AOPs were also investigated to compare the differences between the written and spoken modes. The findings of the study revealed that the undergraduates used same moves of the genre for the introduction, conclusion and question and answer sections. The moves and steps in the body section were different in the both English and discipline based courses as these were determined by the nature of the task and content or the subject matter. However, there were some differences in the move pattern and steps. The results also indicate that knowing the rhetorical structure of the AOP had helped undergraduates transfer genre knowledge of the AOPs from the English language course to the discipline-based courses. The linguistic analysis showed the use of formulaic expressions and metadiscourse markers in the AOPs. Findings indicate similarities and differences of the linguistic features linked to the moves. Additionally, the study also found that content in the visuals and delivery mode was relatively different in both contexts. Undergraduates wrote chunks on their visuals (powerpoint slides) in discipline-based AOPs unlike the English language AOPs which displayed short notes. Despite being trained to avoid reading from the visuals in the English language proficiency classes, the study found that the undergraduates read a lot from the visuals. The use of the rhetorical moves and steps as well as the linguistic features reflected their generic understanding of the AOP. In conclusion, the study demonstrated that knowing the rhetorical structure of the AOPs can help transfer the generic knowledge from one course to other courses in their discipline. The pedagogical implications of this study are that the results obtained may assist English language lecturers in preparing appropriate materials and activities to foster genre awareness that can guide undergraduates to equip themselves with generic knowledge that can be transferred from one context to another. Moreover, lecturers may prepare for the areas of weaknesses such as making short notes. By knowing the generic structure of academic oral presentations, undergraduates can perform better as presenters and acquire effective communication skills. The findings of the similarities and differences of the academic oral presentations in English language and discipline-based classes also suggest that faculties work together to make academic oral presentations more meaningful and relevant for the benefit of the undergraduates.